Capital Structure and Asset Growth on Firm Value: Profitability as a Mediating Factor in the Economic Development of Manufacturing Companies Listed on the Indonesia Stock Exchange - Haerunnisah, Haerunnisah; Hermuningsih, Sri; Damanik, Johannes Maysan (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of capital structure and asset growth on firm value with profitability as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This study uses secondary data in the form of annual financial reports, with purposive sampling technique based on certain criteria, resulting in 35 companies as samples. The analysis method used is the Sobel test to test the mediating role of profitability in the relationship between capital structure, asset growth, and firm value. The results showed that capital structure and asset growth each have a positive and significant effect on firm value. Profitability is also proven to mediate the effect of capital structure and asset growth on firm value significantly. Optimal capital structure and directed asset growth can increase profitability, which in turn has a positive impact on firm value. This study provides implications for company management to pay more attention to managing capital structure and asset growth in order to increase profitability, which can be the main strategy to maximize firm value in the capital market.